(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article provides details on the essential aspects of creating a lexicographic description of concepts, emphasizing the consideration of a word’s semantic structure. It also covers the importance of incorporating semantic components as core, periphery, and associative fields when describing a concept, enabling a more comprehensive understanding of a word’s meaning and use in various contexts. Additionally, the thesis asserts that the fundamental essence of a concept, as determined by lexicographic analysis, represents the most basic and general aspect of the conceptual content, reflecting primarily minimal elements.